Penerapan Model Pembelajaran Teams Games Tournament Untuk Meningkatkan Hasil Belajar Siswa Kelas 1 SDN Sidomulyo Kec. Semen - Moh. Izzudin Arrozi; Reo Prasetiyo Herpandika; Rina Agus Pambudi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine the improvement of student learning outcomes by using the cooperative learning model teams games tournament in the subject of PJOK. The research method used is classroom action research (CAR). The subjects of this study were grade 1 elementary school students. The subjects consisted of one class consisting of 22 students. The results of the study showed that student learning outcomes increased in each cycle. The average value of students increased in the pre-cycle stage, getting an average score of 72, in cycle 1 80, and in cycle 2 83. Similarly, the percentage of completeness also increased, namely in the pre-cycle 45%, in cycle 1 getting 77%, and in cycle 2 getting 86%. The application of this cooperative learning model can also increase student learning activities. Student learning activities are directed according to the learning model used so that the learning process can take place properly. Based on the results of the study, the application of this TGT cooperative learning model can improve student learning outcomes and the percentage of student completeness in the subject of PJOK.